Cross-Border E-Crimes: Jurisdiction and Due Process Challenges - AllahRakha, Naeem (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
Cross-border e-crimes pose significant challenges due to the borderless nature of cyberspace and the complexities of international legal cooperation. This research examines the existing international legal frameworks, such as the Budapest Convention on Cybercrime, and their effectiveness in harmonizing laws and facilitating cross-border investigations. The study applies the doctrinal research methodology to analyze the regulations on cybercrimes. It analyzes the role of international standards of due process and prosecution in upholding individual rights and ensuring fair trials in cross-border cases. The legal frameworks for collecting and sharing digital evidence across borders are fragmented, creating significant challenges for international cooperation. Emerging technologies further complicate the governance of cybercrime. Law enforcement agencies face legal and privacy issues when accessing cross-border data stored in the cloud. The execution of mutual legal assistance requests in cybercrime cases remains slow and inefficient. Gaps in international frameworks hinder lawful access to electronic evidence, while cross-border cybercrime investigations experience delays due to language barriers, incompatible laws, and limited technical expertise within national agencies. These challenges underscore the need for a unified approach to tackle cross-border e-crimes effectively.